Reconciling the Ledger: The Rupert’s Land Purchase, Settler Capitalism, and Indigenous Dispossession on the Prairies - McKenzie, Elizabeth; Mosby, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2024)
This article examines one of the greatest land grabs in history and what may represent one of the single greatest transfers of wealth from Indigenous peoples to a private company: the so-called Rupert’s Land Purchase of 1870. By comparing the lands and money given to the Hudson’s Bay Company following Confederation for the transfer of Rupert’s Land to Canada with the lands and money set aside for First Nations signatories of Treaties 1–7 (1871–77) and the Métis Nation under the Manitoba Act of 1870, we attempt to establish what this looked like in material terms. In addition to highlighting the scale of wealth dispossession that occurred in both quantitative and qualitative terms, this article is primarily concerned with Canada’s actual implementation of these agreements. In recognizing the treaties beyond their written documents, this article seeks to challenge some of the popular narratives surrounding the Rupert’s Land Purchase and its significance in histories of stolen Indigenous land and wealth.